ANALYSIS OF THE IMPACT OF THE COVID-19 PANDEMIC AND THE WAR WITH RUSSIA ON THE ATTRACTION OF FOREIGN INVESTMENTS IN THE ECONOMY OF UKRAINE - BIELIKOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The COVID-19 pandemic and the war with Russia have negatively affected Ukraine’s agro-industrial complex, resulting in a drop in production, exports and investment, as well as significant damage to agricultural land and infrastructure in areas affected by the conflict. The purpose of the article was to study the impact of such uncontrolled phenomena as the COVID-19 pandemic and the war with Russia on the agro-industrial complex of Ukraine, to identify the main negative factors and to identify directions for improving its functioning. The article summarizes the statements of domestic scientists regarding the impact of COVID-19 and the war on the agricultural sector of Ukraine, highlights the key negative factors of the negative impact, including a reduction in exports, increased market volatility, an increase in the cost of production, transportation and cost of agricultural products, a decrease in investment in the agricultural sector of Ukraine, price fluctuations on goods, and the exchange rate, significant damage to production facilities, a decrease in exports, but positive aspects, such as opportunities for the development of the domestic market, were also identified. Statistical data on the impact on investment flows in the agricultural sector were analyzed, the main problems faced by the sector due to the pandemic and war were highlighted, and measures were proposed to fully reveal its potential as an agricultural center. Adapting to negative factors and exploring potential market opportunities at the domestic and international levels will be crucial for the sector’s recovery and long-term growth, as the combined impact of the COVID-19 pandemic and the ongoing war with Russia has created a multifaceted crisis for Ukraine that has affected its economy, society and geopolitical environment. Efforts to address these challenges will require comprehensive strategies, international support and a commitment to unity and resilience.